Elusive search for effective provider interventions: a systematic review of provider interventions to increase adherence to evidence-based treatment for depression - Pedersen, Eric R. (Implement Sci, 2018)
BACKGROUND: Depression is a common mental health disorder for which clinical practice guidelines have been developed. Prior systematic reviews have identified complex organizational interventions, such as collaborative care, as effective for guideline implementation; yet, many healthcare delivery organizations are interested in less resource-intensive methods to increase provider adherence to guidelines and guideline-concordant practices. The objective of this systematic review was to assess the effectiveness of healthcare provider interventions that aim to increase adherence to evidence-based treatment of depression in routine clinical practice. METHODS: We searched five databases through August 2017 using a comprehensive search strategy to identify English-language randomized controlled trials (RCTs) in the quality improvement, implementation science, and behavior change literature that evaluated outpatient provider interventions, in the absence of practice redesign efforts, to increase adherence to treatment guidelines or guideline-concordant practices for depression. We used meta-analysis to summarize odds ratios, standardized mean differences, and incidence rate ratios, and assessed quality of evidence (QoE) using the GRADE approach. RESULTS: Twenty-two RCTs promoting adherence to clinical practice guidelines or guideline-concordant practices met inclusion criteria. Studies evaluated diverse provider interventions, including distributing guidelines to providers, education/training such as academic detailing, and combinations of education with other components such as targeting implementation barriers. Results were heterogeneous and analyses comparing provider interventions with usual clinical practice did not indicate a statistically significant difference in guideline adherence across studies. There was some evidence that provider interventions improved individual outcomes such as medication prescribing and indirect comparisons indicated more complex provider interventions may be associated with more favorable outcomes. We did not identify types of provider interventions that were consistently associated with improvements across indicators of adherence and across studies. Effects on patients’ health in these RCTs were inconsistent across studies and outcomes. CONCLUSIONS: Existing RCTs describe a range of provider interventions to increase adherence to depression guidelines. Low QoE and lack of replication of specific intervention strategies across studies limited conclusions that can be drawn from the existing research. Continued efforts are needed to identify successful strategies to maximize the impact of provider interventions on increasing adherence to evidence-based treatment for depression. TRIAL REGISTRATION: PROSPERO record CRD42017060460 on 3/29/17 ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s13012-018-0788-8) contains supplementary material, which is available to authorized users.